Tristan Tzara’s Poetical Visions: Ironic, Oneiric, Heroic - Ruth Caldwell (Studies in 20th & 21st Century Literature, 2012)
Tristan Tzara is most often associated with Dada, a movement whose influence has often been overlooked. However, Tzara stands out among his peers because of his extensive production of poetical works associated not only with Dada but surrealism and beyond. In all of these texts we see a constant refusal to be complacent about artistic endeavor or the world around us. His Dada texts launch an attack on language by the use of irony and a tension of the text against itself. This internal tension becomes the struggle depicted in his surrealistic epic, L’Homme approximatif, an unfulfilled search for a cosmic language. Tzara’s postwar poetry reflects Tzara’s continuous political commitment as well as his ongoing use of irony and dream imagery in order to attempt to redefine the human situation. His critiques of war, commercialism, language and our relation to the natural world are still relevant in the twenty-first century.
Keywords: Tzara; poetry; surrealism; modernism; Dada; self; L& #x27; Homme approximatif; war; commercialism; nature